THE ROLE OF BLOOD DILUTION IN THE ASPIRIN AN TIPYRESIS - GUERRA, FANY B (UNIVERSIDAD NACIONAL AUTONOMA DE MEXICO, FACULTAD DE MEDICINA, DEPARTAMENTO DE FARMACOLOGIA EXPERIMENTAL, CD. MEXICO, DF, MEX, 1977)
The anterior hypothalamic areas, by producing blood dilution and water shifts, indicate the body responses to environmental heating, fever and aspirin administration An opposite effect, ie, plasma concentration is present as a response to cold and duri
J PHARMACOL EXP THER
Keywords: ROLE, BLOOD, DILUTION, ASPIRIN, TIPYRESIS; CIENCIAS MEDICAS; FARMACOLOGIA; FARMACOLOGIA EXPERIMENTAL